1995
DOI: 10.1002/jcp.1041620214
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of response kinetics to the response pattern: Studies of responses to thyrotropin‐releasing hormone in Xenopus oocytes

Abstract: In Xenopus oocytes injected with total rat pituitary GH3 cell RNA, thyrotropin-releasing hormone (TRH) causes the activation of the inositol lipid transduction pathway and the induction of chloride conductance via calcium-activated channels (Oron et al., 1987, Mol. Endocrinol., 1:918-925). This response exhibits characteristic prolonged latency (Oron et al., 1988, Proc. Natl. Acad. Sci. U.S.A., 85:3820-3824; Lipinsky et al., 1993, Pflugers Arch., 425:140-149). We examined the role of agonist diffusion in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The involvement of [Ca 2+ ] i in desensitization suggested that one of the calcium‐sensitive steps in the signalling pathway might be mediating this effect. Since our previous results suggested that rapid desensitization of the response to TRH in Xenopus oocytes was partially mediated by PKC ( Lipinsky et al ., 1995a , 1995b ), we tested the role of PKC in desensitization of cells expressing C335Stop TRH‐Rs. Two different approaches were employed: down‐regulation of PKC by chronic exposure to PMA ( Glikes et al ., 1994 ), and inhibition by chelerythrine, a specific inhibitor of PKC ( McFerran & Guild, 1994 ; McFerran et al ., 1995 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of [Ca 2+ ] i in desensitization suggested that one of the calcium‐sensitive steps in the signalling pathway might be mediating this effect. Since our previous results suggested that rapid desensitization of the response to TRH in Xenopus oocytes was partially mediated by PKC ( Lipinsky et al ., 1995a , 1995b ), we tested the role of PKC in desensitization of cells expressing C335Stop TRH‐Rs. Two different approaches were employed: down‐regulation of PKC by chronic exposure to PMA ( Glikes et al ., 1994 ), and inhibition by chelerythrine, a specific inhibitor of PKC ( McFerran & Guild, 1994 ; McFerran et al ., 1995 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous observations in oocytes led us to postulate that the very rapid desensitization caused by limited occupancy of TRH‐R is mediated, at least in part, by PKC ( Lipinsky et al ., 1995a , 1995b ). In cells expressing WT TRH‐Rs, acute activation of PKC appears to dramatically inhibit TRH responses: in AtT20 cells by 75–96% ( Perlman & Gershengorn, 1991 ), and in Xenopus oocytes by more than 90% ( Lipinsky et al ., 1995b ).…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that changes in extracellular pH can significantly improve the binding of TRH to its receptor and, thus, shorten the latency of the response, without affecting its amplitude. Moreover, our previous results indicate that the binding process does not contribute to the latency of the response (Lipinsky et al, 1995a). Also, Perlman et al (1992) have proposed that the binding of TRH to its receptor does not involve ionic interactions and is mostly pH-insensitive between pH 6.6 and 9.5.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, the response latency provides a temporal window for integration of external signals that affect the amplitude of the response (Lipinsky et al, 1995a) and its desensitization (Lipinsky et al, 199513). The binding of guanine nucleotides to G-proteins may be affected by …”
mentioning
confidence: 99%